If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(2h + -1) + 13 = 9 Reorder the terms: 6(-1 + 2h) + 13 = 9 (-1 * 6 + 2h * 6) + 13 = 9 (-6 + 12h) + 13 = 9 Reorder the terms: -6 + 13 + 12h = 9 Combine like terms: -6 + 13 = 7 7 + 12h = 9 Solving 7 + 12h = 9 Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + 12h = 9 + -7 Combine like terms: 7 + -7 = 0 0 + 12h = 9 + -7 12h = 9 + -7 Combine like terms: 9 + -7 = 2 12h = 2 Divide each side by '12'. h = 0.1666666667 Simplifying h = 0.1666666667
| 9m^3n+4m^3n+5mn= | | x=100-4(3)(3) | | 5-2(m+1)=3m-2 | | 3y+30=15+5Y | | 3+1/2x+2/3x+5=41/2 | | (3/4+1/2)/4/7 | | (50x^8+10x^7+x^6)/10x^3 | | S=34t+232 | | -18v+6=10+5t | | -2(a+3)=4a-3 | | v-(5/8)=(-1/2) | | c-5=1-3 | | 2y+34=12+5y | | z+(z-6)=-10 | | 15=9+v/2 | | v-(5/8)=1/2 | | ((81k^-3)^2)/9k^9=0 | | X=-24+9x | | 6k-(8+k)=-(6k+8) | | 8+6(9-5)(9-5)= | | 5x-34=9 | | x/4+100=150 | | 24.36/12=x/8 | | X+24=9x | | 5+b=-15-3 | | 2[x-[x-(x-1)]]+(x+2)=256 | | -13+5(1+4m | | -13+5(1+4m | | -5(4n-7)=60 | | 3(v-2)=5v+7-2(-8v-1) | | 10m-10-5m=60 | | 4x^3-35x^2+36x-9=0 |